Accuracy of coordinate determinations of the network of protected zone points according to the results of GNSS observations - Tereshchuk, Oleksiy; Kryachok, Sergiy; Belenok, Vadym (Geodesy and Cartography, 2022)
The article examines errors of the planned position of the points of the educational and research site “Fortuna” of the Chernihiv Polytechnic National University (Ukraine), located in a forested area. Kinematic positioning has been performed using a GNSS receiver GeoMax Zenith 10/20 in real time mode. The network of permanent satellite GNSS stations System NET has been used as a coordinate basis. RTK Master Auxiliary Corrections (MAX) technology has been used to form the corrective amendments. The calculation of RTK corrections has been performed using the software package Leica GNSS Spider v4.3. The Transverse Mercator cartographic projection has been used to determine the flat rectangular coordinates in the USK-2000 system. The values of the coordinates determined in the RTK mode have been compared with the coordinates obtained by the method of electronic polygonometry, which are estimated to be 3 times more accurate. Coordinate differences have formed error vectors. As a result of analysis of the vector field, a stable tendency has been established: the deviation of the planned coordinates of the site points, determined by the method of GNSS-observations in real time mode and located in the forest park zone, in the direction of the base station.